Spirulina as an animal feed and its effect on animal health and productivity - Waheed, Doaa M.; El-Diasty, Mohamed; Gabr, Elsayed M. (Journal of Advanced Veterinary Research, 2024)
The extraordinary increase in demand for animal protein such as meat, eggs, milk, and other animal products, as well as the large quantities of protein feed inputs required for animal production, have principally spurred research into spirulina as an animal feed. Spirulina (Athrospira sp.) is a highly nutritious edible microalga and a prospective feed supply for many agriculturally significant animal species. Animal growth, fertility, beauty, and nutritional product quality have all been linked to spirulina. Spirulina consumption has been related to improved animal health and well-being in studies. Because of its nutritious and protein-rich composition, its impact on animal development was significant, and commercial production was raised to suit consumer demand. As a result, Spirulina is emerging as a cost-effective resource for increasing animal output in order to achieve long-term sustainability and a viable food security future.